PENGARUH DEBT TO EQUITY RATIO DAN UKURAN PERUSAHAAN TERHADAP YIELD TO MATURITY OBLIGASI KORPORASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Renny Mointi (Jurnal Bisnis dan Kewirausahaan, 2017)
The purpose of this study is to analyze, prove and know the effect of debt to equity ratio and firm size on the yield to maturity of corporate bonds at companies listed on the Indonesia Stock Exchange. The analysis method used is multiple regression analysis, partial significance test (t test) and global test (F test) using SPSS assistance. The observation period is 2 (two) years from 2013 until 2015. The results of this study indicate that the debt to equity ratio has a positive and significant effect on the yield to maturity of bonds and firm size (total assets) have a negative and significant effect on yield to maturity of bonds